An ICT Tool in a Rural School: A Drawback for Language Students at School? - Rojas Rojas, Yehison Andrés (Universidad Pedagógica y Tecnológica de Colombia, 2019)
Technology involves a vast number of advantageous usages that range from the sciences to the educational settings. Limited access to computers and the internet, among other factors, are a drawback, thus, creating a digital gap. Nonetheless, the panorama for English as a Foreign Language (EFL) and the use of internet communication technologies (ICT) in Colombia is promising given the countless number of new resources found online. However, using ICT tools requires not only the teacher’s attention, but also governmental aid before they can be implemented in the EFL class. The scope of the ICT tools in the rural setting is vast and has a great impact on students. Therefore, if factors, such as equipment in decent conditions, updated applications, and training, are not provided the real amplitude of these tools cannot be measured.